(untitled) (Research, Society and Development, 2022)
Objective: to analyze the cases of flu-like syndrome in adolescents, the tests performed and the presence of comorbidities in this group. Method: This is a cross-sectional study, accomplished in the period of May 2020 to July 2020, with secondary data from 6,988 patients with flu-like syndrome. The variables analyzed were: age group, gender, race, types of tests performed and results for detection of c, presence of comorbidities. The statistical data were analyzed in SPSS version 20, that was used simple and relative frequencies. Results: The most of adolescents were between 15 and 19 years old (70.5%) and are female (55%). The majority of people (51.3%) declared themselves brown/black, 52% of the adolescents had tests, resulting in 19% of positive cases for Covid-19. 8.6% of people with comorbidities were identified with chronic respiratory disease (5%), followed by diabetes (1%), and heart disease (0.8%). We identify16 deaths, seven were related to Covid-19. Conclusion: It is important to consider the presence of other flu-like syndromes that may have affected the health of adolescents, unfortunately due to lack of registration can not be reported that these syndromes in the future. The tests showed few cases of positivity for Covid-19 in the analyzed period.